External Counterpulsation Improves Angiogenesis by Preserving Vascular Endothelial Growth Factor-A and Vascular Endothelial Growth Factor Receptor-2 but Not Regulating MicroRNA-92a Expression in Patients With Refractory Angina - Ambari, Ade Meidian; Lilihata, Gracia; Zuhri, Ervan; Ekawati, Elok; Wijaya, Shoma Adhi; Dwiputra, Bambang; Sukmawan, Renan; Radi, Basuni; Haryana, Sofia Mubarika; Adiarto, Suko; Hanafy, Dicky A.; Zamroni, Dian; et al. (Frontiers in Cardiovascular Medicine, 2021)
Objective: External counterpulsation (ECP) provides long-term benefits of improved anginal frequency and exercise tolerance in patients with refractory angina (RA). This is postulated as a result of improved angiogenesis and endothelial function through an increase in shear stress. Angiogenesis is mainly represented by vascular endothelial growth factor-A (VEGF-A) and its receptor, vascular endothelial growth factor receptor-2 (VEGFR-2). The microRNA-92a (miR-92a) is a flow-sensitive miRNA that regulates atherosclerosis and angiogenesis in response to shear stress. Thus, ECP beneficial effect might be achieved through interaction between VEGF-A, VEGFR-2, and miR-92a. This study aims to evaluate the ECP effect on VEGF-A, VEGFR-2, and miR-92a in patients with RA in a sham-controlled manner. Methods: This was a randomized sham-controlled trial, enrolling 50 patients with RA who have coronary artery disease (CAD). Participants were randomized (1:1 ratio) to 35 sessions of either ECP (n = 25) or sham (n = 25), each session lasting for 1 h. Plasma levels of VEGF-A and VEGFR-2 were assayed by the ELISA technique. The quantitative reverse transcription-polymerase chain reaction (qRT-PCR) was performed to measure miR-92a circulating levels in plasma. Result: External counterpulsation significantly preserved VEGF-A and VEGFR-2 level compared to sham [ΔVEGF-A: 1 (−139 to 160) vs.−136 (−237 to 67) pg/ml, p = 0.026; ΔVEGFR-2: −171(-844 to +1,166) vs. −517(−1,549 to +1,407) pg/ml, p = 0.021, respectively]. Circulating miR-92a increased significantly in ECP [5.1 (4.2–6.4) to 5.9 (4.8–6.4), p < 0.001] and sham [5.2 (4.1–9.4) to 5.6 (4.8–6.3), p = 0.008] post-intervention. The fold changes tended to be higher in ECP group, although was not statistically different from sham [fold changes ECP = 4.6 (0.3–36.5) vs. sham 2.8 (0–15), p = 0.33)]. Conclusion: External counterpulsation improved angiogenesis by preserving VEGF-A and VEGFR-2 levels. Both ECP and sham increased miR-92a significantly, yet the changes were not different between the two groups. (Study registered on www.clinicaltrials.gov, no: NCT03991871, August 8, 2019, and received a grant from the National Health Research and Development of Ministry of Health of Indonesia, No: HK.02.02/I/27/2020).